Ultrasonic Surgical Techniques for the Pelvic Surgeon - Rader, Janet S.; Rosenshein, Neil B. (Springer New York, 1995)
Ultrasonic surgical techniques were first used by Dr. Kelman in the 1960s to fragment cataracts through a 2-mm incision allowing for minimally invasive surgery. The results from this procedure stimulated the development of a larger, move powerful ultrasonic unit that was used in neurosurgery. This instrument allowed the neurosurgeon to selectively remove tumor tissue with decreased blood loss and tissue trauma. The ability now of ultrasonic equipment to selectively fragment, irrigate, and aspirate tissue with minimal coagulation effect spurred its rapid use in surgery on the liver, spleen, kidney, and other intra-abdominal organs. This instrument has been invaluable in ovarian cancer cytoreduction and intricate segmental organ resection. The newest technical developments include electro cautery capability built into the hand piece and extended hand pieces for laparoscopic surgery. The impetus for assembling this volume has been to provide an extensive review of the field of ultrasonic surgery as it has currently developed including principles, equipment features, and surgical tech niques. It is hoped that the information will be of use to physicians in training and surgeons in practice. The book takes a multidisciplinary approach with chapters authored by a diversity of subspecialists in gen eral surgery, urology, surgical oncology, and gynecologic oncology. Each chapter contains basic information on surgical techniques. Together, these chapters cover surgery of the GI tract, kidney, liver, and lower genital tract, and present a number of personal approaches